Implementasi Kebijakan Parkir Di Kawasan Tertib Lalu Lintas Jalan Jendral Ahmad Yani (Pengkolan) Kabupaten Garut - Pundenswari, Pupung; Rizky, Fikry Munawar (Jurnal Publik, 2022)
This study the implementation of parking policies in the Orderly Traffic Area of ??Jalan Jendral Ahmad Yani (Pengkolan) Garut Regency. This study uses qualitative methods with descriptive analysis. Data collection techniques used observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation and drawing conclusions. In implementing the policy, local governments carry out persuasive communications through various media and counseling, take firm action in the form of raids and eviction of motorized vehicles parked illegally in the Pengkolan area. The human resources for implementing the policy, Department of Transportation and Satpol PP, are sufficient both in quality and quantity. Official parking facilities are still limited and cannot accommodate the number of vehicles. The inhibiting factors are the lack of enforcement of sanctions, the lack of outreach to the people who come to the Pengkolan area, the lack of public understanding of the function of official parking lots. As for suggestions, the local government should look for parking facilities that are close to shops in the Pengkolan area, take strict action against illegal parking that is rampant along Pengkolan, maintain the attitude of the apparatus who have a strong commitment to achieving K3 Pengkolan.